In-Season vs. Out-of-Season Academic Performance of College Student-Athletes - Brianna M. Scott; Thomas S. Paskus; Michael Miranda; Todd A. Petr; John J. McArdle (University of Kansas Libraries, 2008)
There is a commonly held belief within the intercollegiate athletics community that student-athletes perform better academically during their season of athletics competition than they do outside the season of competition. The thought is that the structured nature of the playing season leads to more structure in student-athletes' academic lives and better academic performance. However, it is difficult to find empirical studies supporting this belief. A series of three studies was conducted to assess whether there is a difference in the grade-point average and credits earned of student-athletes in their season of competition vs. their off-season. These three studies are distinguished by NCAA membership division (Division I, Division II or Division III) and the specific nature of the data available in each of those divisions. The Division III study served as a pilot and examined over 3,000 student-athlete records at eight schools. The Division II study included nearly 12,000 student-athletes at 92 schools, and the Division I study involved analysis of a census of Division I student-athletes at over 325 colleges and universities followed term-by-term for up to four years. The separate divisional studies came to similar conclusions. Generally, the academic performance of student-athletes was shown to be better outside the season of competition than during the season-contrary to the conventional wisdom. The negative in-season effects were stronger in sports known to have high in-season time demands (e.g., Division I football, baseball and softball) and among student-athletes who entered college less well prepared academically.